The Potential Role of Science, Technology, Engineering, and Math Programs in Reducing Teen Dating Violence and Intimate Partner Violence. - D'Inverno, Ashley Schappell; Kearns, Megan C.; Reidy, Dennis E. (Journal of Women's Health (15409996), 2016)
Science, technology, engineering, and math (STEM) are growing fields that provide job stability, financial security, and health prosperity for professionals in these fields. Unfortunately, females are underrepresented in STEM, which is potentially both a consequence and precipitant of gender inequity in the United States. In addition to the financial and health benefits, increasing the number of girls and women in STEM fields may also indirectly prevent and/or reduce teen dating violence and intimate partner violence by: (1) increasing women's financial independence, thereby reducing dependence on potentially abusive partners; (2) decreasing household poverty and financial stress, which may lead to reductions in relationship discord; and (3) increasing attitudes and beliefs about women as equals, thereby increasing gender equity. In this commentary, we discuss the potential role of primary and secondary school STEM programs in reducing violence against women. We review the literature on existing evaluations of STEM programs for educational outcomes, discuss the limitations of these evaluations, and offer suggestions for future research.